Beyond Longevity: How Gender Roles Shape the Ageing Experience of Women in Nigeria - Oluwatobi (Magyar Gerontológia, 2025)
Longevity is often celebrated as a marker of progress in global ageing discourse. Yet for many Nigerian women, a longer lifespan does not necessarily translate into security, dignity, or empowerment in later life.